Pengaruh Adopsi Fintech dan Literasi Keuangan terhadap Kinerja Keuangan dengan Kepercayaan Digital sebagai Variabel Moderasi pada Bank Syariah - Pamikatsih, Mutia Pamikatsih; Cahyaningsih, Regita Cahyaningsih (Jurnal Bisnis dan Kewirausahaan, 2025)
This study investigates the influence of Fintech Adoption and Financial Literacy on the Financial Performance of Islamic banks in Indonesia, with Digital Trust examined as a moderating variable. Utilizing a quantitative approach and Partial Least Squares Structural Equation Modeling (PLS-SEM), data were collected from 150 managerial respondents across 14 Islamic commercial banks. The findings reveal that Fintech Adoption significantly and positively affects Financial Performance (p < 0.05), highlighting the strategic importance of digital transformation in the banking sector. However, Financial Literacy does not demonstrate a significant impact, nor does Digital Trust significantly moderate either the Fintech Adoption–Performance or Financial Literacy–Performance relationships. These results suggest that organizational-level factors and system integration may play a more decisive role than individual competencies or perceived trust in shaping performance outcomes. Theoretically, this research reinforces the Technology-Organization-Environment (TOE) framework while challenging assumptions from Human Capital and Trust-Based Models. The study’s practical implication emphasizes prioritizing digital infrastructure development over isolated staff training in Islamic banking. Limitations include its cross-sectional design and institutional focus, prompting future research to adopt multi-level and longitudinal approaches. This study contributes to the growing discourse on digital finance within faith-based financial institutions.